A Comparative Study of Electronic Commerce ODR: Legal Challenges and Reform Perspectives in China and Indonesia - Zuo Xiangbin; Nur Khalidah Dahlan; Haniff Ahamat (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
This article examines the differentiated development paths of Online Dispute Resolution (ODR) systems in China and Indonesia, two core digital economies in ASEAN. China has established a centralized ODR framework through its “E-commerce Law,” which strengthens the enforcement of awards via a judicial coordination model. However, the exclusion of ad hoc arbitration in the “Arbitration Law” limits the effectiveness of platform autonomous awards (internal platform rulings). In contrast, Indonesia relies on platform autonomy, with platforms such as Tokopedia handling disputes. However, enforcement issues for mediation agreements arise from the absence of central legislation, fragmentation of jurisdiction across islands, and the failure of the Arbitration Law to recognize temporary arbitration (ad hoc arbitration). Shared challenges faced by both countries include barriers to mutual recognition of cross-border rulings, lack of technical standards, and privacy protection conflicts due to data localization policies. This article provides several policy recommendations: China should amend the Arbitration Law to recognize the validity of temporary arbitration and establish a national ODR data center to streamline the judicial confirmation process. Indonesia needs to quickly set up a central judicial certification center to make sure that all of its outer islands follow the same rules. This can be done by changing the E-commerce Law and the Arbitration Law. At the regional level, ASEAN should learn from the EU’s ODR platform by creating a system that recognizes certain cross-border rulings and setting up a data exchange center that balances Indonesia’s data storage needs with Singapore’s rules for sharing data across borders. The results supplement to legal reform scholarship by offering practical solutions for integrating ODR systems and harmonizing cross-border dispute resolution across ASEAN, fostering a dynamic adaptation of technical justice to legal authority in the digital age.